Problem-Solving Skills on Prospective Teachers: Digital Problem-Based Learning in Geometry - Koroh, Taty Rosiana; Bulu, Vera Rosalina; Nawa, Netty E. A.; Benu, Adam; Andini, Fransiska (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to determine whether using a digital problem-based learning strategy improves the problem-solving skills of prospective elementary school teacher education students. The research is quantitative and uses a quasi-experimental design. This study implemented a nonequivalent control group design. This study included 66 students divided into two groups: an experimental class using the digital problem-based learning model and a control class using the problem-based learning model. Data were collected using pretest and posttest instruments in both courses before and after the therapy, as well as a questionnaire to assess the attractiveness of learning using the DPBL learning paradigm. The N-gain technique was used to examine the effectiveness of the DPBL model on the problem-solving abilities of prospective elementary school teacher students. The results show an N-gain value of 0.69, which is quite effective when interpreted using N-gain criteria. This means that the digital problem-based learning model can help improve the problem-solving skills of prospective elementary school teacher education students.